Kesiapan Guru dalam Mengembangkan Modul Berbasis STEM untuk Mendukung Pembelajaran di Abad 21 - Diana, Nana; Turmudi, Turmudi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
Nowadays, students' expected comprehensions are not only capable in memorizing formal concepts, but also capable in constructing their knowledge in solving contextual problems. The presence of the STEM approach, which is the integration of four knowledge including Science, Technology, Engineering and Mathematics, considered as one of the appropriate innovations for students in establishing their own knowledge. However, there are several problems that occur in implementing STEM approach in learning, including the preparation for STEM learning. Hence, this study aims to investigate the readiness of teachers in Indonesia to implement STEM learning, in terms of their knowledge about STEM and experience in arranging STEM-based modules. This research was conducted online using a questionnaire which was distributed through google form. Several teachers were also interviewed to get confirmation of their answers on the google form. The subjects in this study consisted of 54 Mathematics and Science teachers in junior high school. After the data was obtained, the data were analyzed qualitatively. Based on this research, it is known that most of the teachers who participated in this study did not have adequate knowledge regarding STEM, so that teachers were struggling in developing STEM-based modules.